IMPLEMENTASI E-GOVERNMENT TRANSFORMASI DIGITAL LAYANAN KEPEGAWAIAN “SITAGUH” PADA BADAN KEPEGAWAIAN DAERAH PROVINSI KALIMANTAN TENGAH - Oktobrian, Ivan; Bernardianto, Raden Biroum; Saipul, Saipul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study explores the implementation of digital transformation in civil service management through the